0002 Integrative geospatial technologies for child injury prevention: spatial analysis of hospital injury data and spatial video surveys of pedestrian and bicycle behaviours in the city of akron and summit county, Ohio. (26th April 2015) - Curtis, Jacqueline; Schuch, Laura; Curtis, Andrew; Hudson, Courtney; Wuensch, Heather
Abstract : Statement of purpose: Though it is widely acknowledged that place affects health, the pathways through which this relationship is realised are not fully understood. Geospatial technologies, such as Geographic Information Systems (GIS) and Global Positioning System (GPS) – enabled devices, offer insights into the health-place nexus through data collection and analysis at fine spatial scales. The purpose of this project is to leverage these geospatial technologies to identify places of risk for child injury. With improved understanding of where children are at elevated risk, prevention measures can then be spatially targeted and evaluated for improved outcomes. Methods/Approach: GIS was used to map hospital injury data at the zip code level for 43 injury code classes. Zip codes were scored based on incidence rank to create risk maps for specific types of injuries and for all injuries. Within sample zip codes, spatial video surveys were conducted on child pedestrian and bicycle-related activities. Spatial video is an emergent geospatial technology that enables the encoding of geographic coordinates from the GPS onto high resolution video data. Results of these surveys were mapped in GIS. Results: Injury data reveal a core-periphery pattern of incidence centring on Akron, displaying distance decay away from the city. Several areas within this core persistently ranked as having the highest incidence across most injury code classes. For the spatial video surveys, the most compelling result is that wearing a helmet while riding a bicycle is an anomaly across all observed children throughout the study area. Conclusions: While results from analysis of hospital injury data indicate a need for spatial targeting of injury prevention efforts in the persistent high risk areas of the city and county, results of the spatial video surveys point to a need for more widespread intervention to address the near universal lack of wearing a bicycle helmet. Significance and contribution to the field: Methodologically, novel approaches to spatial data collection and analysis are presented that are replicable and offer integrated insight into child injury risk. Substantively, this project identifies specific locations where intervention strategies should be prioritised. Finally, this project reports on the academic/non-profit partnership that designed and implemented this research, with guidelines on replication for geospatial support.